A living history of immunology - Kendall Arthur Smith (Frontiers Research Topics, 2015)
In the highly competitive world of biomedical science, often the rush to publish and to be recognized as "first" with a new discovery, concept or method, is lost in the hurly-burly of the moment, as "the maddening crowd" moves on to the next "new thing". One of the great things about immunology today is that it has only become mature as a science within the last half-century, and especially within the past 35 years as a consequence of the revolution of molecular immunology, which has taken place only since 1980. Consequently, most of those who have contributed to our new understanding of how the immune system functions are still alive and well, and still contributing. Thus, "A Living History of Immunology" collates many stories from the investigators who actually performed the experiments that have established the frontiers of immunology. Accordingly, this volume combats "revisionist science", by those who want to alter history by telling the stories a different way than actually happened. In this regard, one of the good things about science vs. other disciplines is that we have the written record of what was done, when it was done and by whom. Even so, we do not have the complete story or narrative of how and why experiments were done, and what made the differences that led to success. This volume captures and chronicles some of these stories from the past fifty years in immunology.